2015
DOI: 10.1002/cbic.201500296
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Serine‐Proteinase‐Catalyzed Peptide Splicing in Analogues of Sunflower Trypsin Inhibitor 1 (SFTI‐1)

Abstract: Serine-proteinase-catalyzed peptide splicing was demonstrated in analogues of the trypsin inhibitor SFTI-1: both single peptides and two-peptide chains (C- and N-terminal peptide chains linked by a disulfide bridge). In the second series, peptide splicing with catalytic amount of proteinase was observed only when formation of acyl-enzyme intermediate was preceded by hydrolysis of the substrate Lys-Ser peptide bond. Here we demonstrate that with an equimolar amount of the proteinase, splicing occurs in all the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The incubation of such peptides with equimolar amounts of proteinase resulted in the synthesis of a peptide bond that gives monocyclic SFTI‐1 inhibitors (Figure ). By applying HPLC/MS and X‐ray analyses, we proved that, regardless of the extension at the C‐ terminus by Ser of the first chain or by Lys at the N‐ terminus of the second chain, spliced monocyclic SFTI‐1 was formed . Using H218O, we confirmed that, similarly to the mechanism of peptide splicing catalyzed by the proteasome, the splicing of SFTI‐1 analogues also follows a direct transpeptidation mechanism.…”
Section: Introductionmentioning
confidence: 61%
“…The incubation of such peptides with equimolar amounts of proteinase resulted in the synthesis of a peptide bond that gives monocyclic SFTI‐1 inhibitors (Figure ). By applying HPLC/MS and X‐ray analyses, we proved that, regardless of the extension at the C‐ terminus by Ser of the first chain or by Lys at the N‐ terminus of the second chain, spliced monocyclic SFTI‐1 was formed . Using H218O, we confirmed that, similarly to the mechanism of peptide splicing catalyzed by the proteasome, the splicing of SFTI‐1 analogues also follows a direct transpeptidation mechanism.…”
Section: Introductionmentioning
confidence: 61%
“…With respect to ultra-high-resolution data collection, the crystal structure of the sunflower trypsin inhibitor 1 (SFTI-1) (Karna et al, 2015) and the structures of open and closed states of Candida antarctica lipase B (Stauch et al, 2015) were determined at 0.91 Å resolution using X-rays at = 1.00 Å (12.4 keV) and = 0.826 Å (15.0 keV), respectively.…”
Section: Highlightsmentioning
confidence: 99%
“…[8][9][10][11] Moreover, the very small size, strong inhibitory and high hydrolysis stability 12,13 of SFTI-1 have made it an excellent scaffold 14 for protein engineering. [15][16][17][18][19][20] Sequences with completely novel function can be graed into the SFTI-1 framework, for engineering of radiopharmaceuticals, antimicrobials, proangiogenic compounds, and rheumatoid arthritis and autoimmune disease peptides. [21][22][23][24][25][26][27][28] SFTI-1 binds to trypsin in a substrate manner but can resist proteolysis for a quite long time.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of either a disulde bond or cyclic backbone showed decreased proteinase resistance to trypsin and inhibitory activity. 6,13,20,[29][30][31][32] The studies on two monocyclic analogs of SFTI-1 showed that the one keeping head-to-tail cycle was remarkably faster hydrolyzed than the with a disulde bridge. 13 On top of it, the hydrogen-bond network also appears to be a crucial determinant of the function of SFTI-1.…”
Section: Introductionmentioning
confidence: 99%